The Empirical Foundations of Self-Efficacy in Physical Education: A Comprehensive Literature Review - Li, Penglian; Ahamed, Forbis; Norshafarina Binti Shari (International Journal on Integrated Education, 2025)
Self-efficacy is a crucial factor influencing the health and well-being of adolescents. This study conducts a comprehensive analysis of the application of self-efficacy theory in physical education, examining its historical development, theoretical underpinnings, and its influence on the health and well-being of adolescents. Studies have shown that social support significantly enhances self-efficacy among adolescents, which in turn plays a crucial role in their learning, health behaviors, and emotional regulation. The study provides specific guidance for educational administrators anempower physical education teachers to improve the health and well-being of adolescents based on empirical evidence.